Women's Suffrage Memorabilia: An Illustrated Historical Study - Florey, Kenneth (McFarland & Company, Inc., 2013)
"This work analyzes 70 different categories of suffrage memorabilia, while providing numerous images of relevant objects along the way, and discusses these innovative production methods. Most important, this study looks at period accounts, often fascinating, of how, why, when, and where the memorabilia were used in both America and England"–
Keywords: Collectibles; Women; Great Britain; Suffrage; United States; Women; Women; dept.eng; faculty_collection